Analiza krajših programov institucionalne predšolske vzgoje - Lepičnik-Vodopivec, Jurka (Šolsko polje, 2008)
In the paper we present the results of the research conducted in spring 2006 on a sample of kindergartens in Slovenia, which offer shorter institutionalized preschool education programmes. We were interested in the selection of shorter programmes, how many hours they each take, what is the age structure of children in those programmes and whether there are any statistically relevant differences between the shorter programmes in regard towhether they are being offered by a public or a private (independent) kindergarten or in a kindergarten at an elementary school. We also tried to establish to what extent the goals and the fields of activity of the kindergarten curricula are being realized and implemented. The results of the research work show that a half of urban kindergartens has been offering shorter programmes for at least 16 years, while there are 43% such kindergartens in the rural areas; most independent kindergartens offer shorter programmes that last 3-4 hours per week, while most kindergartens at schools offer programmes with 1-2 weekly hours. The majority of children enter shorter programmes when they are 4 years old. In the evaluation of the curriculum implementation the kindergartens stayed real, as they admitted that the curriculum goals for kindergartens, i. e. the national document, are not being implemented fully.
Keywords: kurikulum; otroški vrtci; predšolska vzgoja; predšolski otroci